Biomedical Professionals in Brazil: the need and training of human resources for health development - Oliveira , Carlo José Freire; Menezes-Silva , Luísa; Faria , Laura Caroline; Oliveira, Waldir César Ferreira (Revista Saúde & Diversidade, 2020)
Introduction: The undergraduate course in Biomedical Sciences has existed in Brazil since 1966. It has expanded strongly in the last two decades and is responsible for training professionals to diagnose and research the causes, effects, and pathological mechanisms of diseases that affect the population. Even after decades of implementation and considering the reasons that led to the creation of the course, the evaluation in which areas these professionals are working is still incipient. Objective: Our aim is to know if the Biomedical Sciences graduates are being absorbed by the market job and in which areas. Methods: The present work is a retrospective cross-sectional observational study, based on the data of the students who had graduated in the Federal University of the Triangulo Mineiro, Brazil, from the first class of the course in 2003, until the second half of 2018. Results: The study has shown that the course of Biomedical Sciences of a Federal institution in Brazil has low evasion and that most of the graduates migrated to post-graduation (62.3%). Moreover, the majority of the professionals are located in the Southwest region of the country and most of them work in one of the specific áreas linked to the course (70.3%). In addition, these professionals are more prone to ingress in the academic area. Conclusion: These findings demonstrate that, despite being disproportionately distributed in the country, there is still demand for these professionals and clearly indicate the importance of the Biomedical Sciences egresses to teaching and research in Brazil.